Pilot Investigation on Assessing the Quality of Banyuasin Disdukcapil Online Services and its Impact on User Satisfaction - Suharmanto, Arvia Fildzah (PT. Lentera Ilmu Publisher, 2023)
This study focuses on evaluating the quality of online services provided by Banyuasin Disdukcapil and its relationship with user satisfaction. Through a pilot investigation, the efficiency and performance of these services were meticulously examined, covering usability, response time, data accuracy, and information security. The study aimed to understand user perspectives and their satisfaction levels to establish correlations between service quality and user sentiment. Methodologically, nine research stages were executed, culminating in the development of a questionnaire based on the WebQual 4.0 method, exploring Usability Quality, Information Quality, Service Interaction Quality, and User Satisfaction. The validity and reliability tests ensured the credibility of the instruments used. The investigation revealed strong positive correlations across all studied aspects: Usability Quality demonstrated high correlations (r count) ranging from 0.703 to 0.785, emphasizing ease of use, clarity, and positive user experience. Information Quality and Service Interaction Quality showed correlations from 0.545 to 0.783, indicating reliability, accuracy, security, and ease of communication. User Satisfaction exhibited correlations between 0.604 and 0.741, highlighting factors influencing user contentment. Validity testing confirmed the suitability of all indicators without the need for removal, while reliability analysis (Cronbach's Alpha) established consistency across variables.